Perjanjian Kemitraan antara Penyedia Aplikasi Nujek dengan Mitra dalam Perspektif Hukum Ekonomi Syariah - Febriani, Hardini; Fateh, Mohammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The phenomenon of the rise of online application-based transportation is currently widely circulating in society, even online motorcycle taxis have emerged based on sharia. This is expected to be able to meet the needs of the community for public transportation that still upholds sharia principles, but the partnership agreement between the Nujek application provider and partners is very vulnerable to problems and legal risks. This study aims to analyze how the Sharia Economic Law reviews the form of cooperation between the Nujek application provider and partners. This research method uses empirical juridical, using a qualitative approach. The results of this study indicate that the form of cooperation between the Nujek application provider and partners is a form of partnership, which when viewed from Sharia Economic Law, is included in the category of syirkah 'inan. However, in practice, syirkah 'inan with partners still has weaknesses. Because Nujek is not responsible for the risks that will occur and does not provide guarantees to partners. so that from the perspective of Sharia Economic Law, the syirkah agreement in the Nujek cooperation with partners is declared fasid (damaged), then the syirkah cannot be carried out before the cause of the fasid is eliminated.